Medical Bacteriology A Practical Approach - Hawkey, P. M; Ed. Lewis, D. A; Ed (Oxford University Press, 2004)
A guide to frequently used procedures in clinical microbiology laboratories. This book is a useful training aid for the diagnostic microbiology laboratory, and is also suitable for microbiologists preparing for higher professional examinations such as membership of the Royal College of Pathologists and the American Board of Medical Microbiology.